Poly[[1,4-bis-(3-aminopropyl)piperazinium] [[dioxouranium(VI)]-di-mu(2),mu(3)-sulfato]] - Doran, M; Norquist, A; O'Hare, D (2003)
The title compound, {(C10H28N4)[(UO 2)2(SO4)4]}n, contains two-dimensional [(UO2)2(SO4)4] 4- layers with 1,4-bis-(3-aminopropyl)piperazinium cations balancing the charge. Each UVI cation is seven-coordinate in a pentagonal bipyramidal geometry, and each sulfate tetrahedron bridges beween two adjacent uranium centres to form layers. © 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.